Ethical issues in environmental management and resource conservation from Islamic perspective - Muyibi, Suleyman Aremu; Mohd. Salleh, Hamzah (IIUM Press, 2011)
Environmental philosophy based on the Qur'an and Prophetic Traditions (Sunnah) is that there is a fundamental link and interdependency between all natural elements which is based on the premise that if man abuses or exhausts one element, the natural world as a whole will suffer direct consequences. The holistic principle of environmental management as applied by the Prophet Muhammad (SAW) is based on three important principles made up of the concepts of tawhid (unity), khilafah (stewardship) and amanah (trustworthy). The Islamic approach to maintaining a balance bet\veen material development and responsibility will be explored as applied in resource conservation and sustainability. The utilization of all natural resources - land, water, air, fire (energy)- forests, oceans - are considered the right and the joint property of the entire humankind and all creation of Allah on earth. Since Man is Khalifatullah (the vicegerent of Allah) on earth, he should take every precaution to ensure the interests and rights of others, and regard his mastery over his allotted piece of land as a joint Ownership with the next generation. Furthermore the Islamic nation has been tenned as (1/111111atan lvasatan) the moderate nation in the Qur'an, a nation that avoids excesses in all things. Thus, Muslims in particular have to utilize the resources provide on earth by Allah (S WT) responsibly for their benefit, honestly maintain and preserve it- use it considerately and moderately, and pass it on to future generations in an excellent condition.